Biomechanical and chemical behavior of various bioactive materials in class II restorations = Desempeño biomecánico y químico de diferentes materiales bioactivos en restauraciones clase II - Ramírez Barrantes, Juan Carlos 1964-
The aim of this in vitro study was to evaluate the biomechanical and chemical behavior of various bioactive materials in class II MOD restorations. Forty-eight standardized class II MOD cavities were prepared in sound extracted human molar teeth. The specimens were divided into four groups according to the restorative material: Group 1 (Filtek™ Z350 XT), Group 2 (Biodentine™ as a liner, and then restored with Filtek™ Z350 XT), Group 3 (Cention N™), and Group 4 (Activa™ Bioactive-Restorative). The samples were tested for fracture resistance by subjecting them to a compressive load in a Universal testing Machine. The failure modes of each specimen were evaluated. The alkalinizing potential and calcium ion release of the materials were measured. SEM-EDAX analyses were also performed for all materials. Data were analyzed using ANOVA and post hoc Tukey test (p<0.05). Group 1 showed the higher fracture resistance (p<0.05). Group 3 had greater fracture resistance values but no statistical difference from Group 4. Biodentine™ showed greater biomineralization potential. Class II MOD restorations of Group 1 displayed the higher fracture resistance; however, it was highly associated with catastrophic failure. Conversely, Biodentine™ presented a more significant bioactivity potential, and its use, as in Group 2, promoted the most favorable failure mode.